Mapping interdisciplinary collaboration in music education: analysis of models in higher education across North America, Europe, Oceania, and Asia - Zhang, Guozhong; Sun, Jian; Sun, Ying (Frontiers in Psychology, 2023)
Interdisciplinary collaboration is an emerging imperative in music education, but current understanding of global practices remains limited. Prior studies have focused narrowly on specific programs within limited geographic areas. However, there is minimal quantitative mapping of initiatives across institutions and regions. Contextual insights explaining regional variations are also scarce. Hence, this study aims to address these gaps by conducting a comprehensive analysis of interdisciplinary programs, partnerships, events, and publications across leading global music institutions using a mixed methods approach. The analysis reveals significant diversity in models and determinants of productivity across regions. For instance, while Europe leads in formal integration and research output, North America prioritizes technology-enabled innovation through media and emerging tools. Partnerships are ubiquitous but focus areas and curricular integration vary. The findings reveal significant diversity in interdisciplinary education practices and formats worldwide, implying a need for contextualized implementation aligned to institutional strengths rather than a one-size-fits-all approach. Therefore, as music education evolves, tailored interdisciplinary strategies that blend local priorities with global best practices are recommended to creatively nurture multifaceted skills and maximize potential for innovation. Thus, this research contributes an invaluable knowledge base to inform evidence-based, nimble policies and frameworks for cultivating cutting-edge, socially engaged musicians and ventures worldwide.